Energy Technology 2016 Carbon Dioxide Management and Other Technologies - Li, Li; Post Guillen, Donna; Neelameggham, Neale; Zhang, Lei; Zhu, Jingxi; Liu, Xuan; Basu, Soumendra; Haque, Nawshad; Wang, Tao; Verhulst, Dirk; Pandey, Amit (The Minerals, Metals & Materials Series,, 2016)
Topics on CO2 sequestration and reduction in greenhouse gas emissions from process engineering and materials for clean energy are covered. Papers addressing sustainable technologies in extractive metallurgy, materials processing and manufacturing industries with reduced energy consumption and CO2 emission are also included, as well as industrial energy efficient technologies including innovative ore beneficiation, smelting technologies, recycling and waste heat recovery. The book also carries contributions from all areas of non-nuclear and non-traditional energy sources, including renewable energy sources such as solar, wind, biomass, etc. The book also emphasizes novel mineral beneficiation, processing, and extraction techniques leading to waste minimization of critical rare-earth materials used in energy systems (e.g., magnets, display and lighting devices).